Knowledge on newborn care and associated factors among mothers of newborns in medical officer of health areas Balapitiya and Karandeniya and practices and problems encountered in the caring of the newborns - Praneeth, T (My University, 2009)
A cross sectional survey was carried out among 425 mothers who attened clinics with babies aged one to one half months and were residing for more than six months in MOH areas Balapitiya and Ambalangoda. An interviewer administered questionnaire, was used to collect data. Data was analyzed using statistical soft wear package SPSS 16.0. There was a statistically significant association between low birth weight and receiving special care immediately after birth (p0.05) and developing health problem at birth (p0.01). Majority of mothers 98.0 percent.